Competitive Industrialization: New Strategy for Peruvian Business Development - Aranaga Manrique, David (2006)
It is viable for national companies to compete successfully in the world globalization process, but for this purpose the promotion of a Strategy is required: Competitive Industrialization, whose fundamental axes are the lines of industrial growth and regional industrial schemes, both developed within the framework of a systemic approach to competitiveness and promoted through business activity that has to create and maintain dynamic competitive advantages.